2020
DOI: 10.1371/journal.pone.0239974
|View full text |Cite
|
Sign up to set email alerts
|

Under five and infant mortality in Chile (1990-2016): Trends, disparities, and causes of death

Abstract: Background Child health has been a health policy priority for more than a century in Chile. Since 2000, new health and intersectoral interventions have been implemented. However, no recent analyses have explored child mortality and equity in Chile, an indispensable input to guide policies towards the achievement of the Sustainable Development Goals, specially, in the context of a deeply unequal country such as many other Latin American countries. Thus, the objectives of this study are to analyze the variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In this study, preterm and low birthweight children were found to be more at risk of dying before celebrating their fifth birthday compared to term birth and normal birth weight, respectively. Increasing risk of mortality with decrease in gestational age at delivery and low birthweight was previously reported [ 30 - 32 ]. Increased risk of death among preterm and low birthweight children born at home was reported due to lack of quality care and treatment for short and long-term health consequences such as hypothermia immediately after birth and in the first days of life [ 33 ].…”
Section: Discussionmentioning
confidence: 88%
“…In this study, preterm and low birthweight children were found to be more at risk of dying before celebrating their fifth birthday compared to term birth and normal birth weight, respectively. Increasing risk of mortality with decrease in gestational age at delivery and low birthweight was previously reported [ 30 - 32 ]. Increased risk of death among preterm and low birthweight children born at home was reported due to lack of quality care and treatment for short and long-term health consequences such as hypothermia immediately after birth and in the first days of life [ 33 ].…”
Section: Discussionmentioning
confidence: 88%
“…A gestational age less than 32 weeks increased the risk of death. Aguilera et al reported a high risk of death in preterm babies in Chile [18]. This is explained by the immaturity of these newborns and their high susceptibility to infections.…”
Section: Factors Associated With Neonatal Mortalitymentioning
confidence: 99%
“…Preventive measures might be crucial in PED-ARI because access to proper care in many places in Latin America and the world is non-available or difficult. Even more, in non-developed regions, there is a correlation between PED-ARI mortality and socioeconomic status between and within countries 17-21 . Recent data show that admission due to PED-ARI has a negative impact on development, even in high-income countries.…”
Section: Discussionmentioning
confidence: 99%